Describing the Patient Journey of Women with Claims for Uterine Fibroids and Heavy Menstrual Bleeding Using a Commercial Database (2011–2020) - Agarwal SK; Stokes M; Kung T; Tilney R; Lickert C (Dove Medical Press, 2023)
Sanjay K Agarwal,1 Michael Stokes,2 Tiffany Kung,3 Rong Tilney,2 Cassandra Lickert3 1UC San Diego, La Jolla, CA, USA; 2Evidera, St. Laurent, Quebec, Canada; 3Myovant Sciences, Inc (now known as Sumitomo Pharma America, Inc), Marlborough, MA, USACorrespondence: Cassandra Lickert, Sumitomo Pharma America, Inc, 4 Waterford Drive, Marlborough, MA, 01752, USA, Tel +1 (708) 214-1007, Email Cassandra.lickert@us.sumitomo-pharma.comIntroduction: This retrospective database claims analysis describes the clinical characteristics and treatment patterns of commercially insured United States women with uterine fibroids (UF) and heavy menstrual bleeding (HMB).Methods: Women age 18- 55 years with an incident UF diagnosis (index date) between 1/1/2012 and 12/31/2019 and ≥ 1 claim for HMB (UF-HMB), were identified from the Optum® Clinformatics® database. Outcomes included clinical characteristics, pharmacologic therapy use, and surgeries/procedures. Regression models were used to identify factors associated with time to post-diagnosis hormonal therapy and hysterectomy.Results: A total of 85,428 women had UF-HMB (mean [SD] age, 43.7 [6.4] years). The median follow-up was 3.2 years. After HMB, the most common symptoms were pelvic pressure/pain (27.6%) and backache (17.5%). Within 6 months of UF diagnosis, 40.2% of patients had received only pharmacologic therapy; 25.5% had received no treatment; 24.3% had a hysterectomy, and 10.0% had other procedures. By the end of follow-up, 50.0% had received a hysterectomy. Multiple factors were predictive of a higher likelihood of receiving hormonal therapy (geographic region, infertility, pre-index pregnancy) or hysterectomy (older age, prior hormonal treatment, specific bulk symptoms, White race).Conclusion: Within 6 months of UF diagnosis, fewer than one-half of women with UF-HMB had received hormonal therapy, one-quarter received no treatment, and one-quarter had received a hysterectomy or another gynecologic procedure. Patients who received a hysterectomy were more likely to be older, White, and to have bulk symptoms.Keywords: uterine fibroids, leiomyoma, heavy menstrual bleeding, menorrhagia